Antibody response against PhoP efficiently discriminates among healthy individuals, tuberculosis patients and their contacts. - Aurobind Vidyarthi; Nargis Khan; Tapan Agnihotri; Kaneez F Siddiqui; Girish R Nair; Ashish Arora; Ashok K Janmeja; Javed N Agrewala (PLoS ONE, 2017)
Tuberculosis continues to be one of the most devastating global health problem. Its diagnosis will benefit in timely initiation of the treatment, cure and therefore reduction in the transmission of the disease. Tests are available, but none can be comprehensively relied on for its diagnosis; especially in TB-endemic zones. PhoP is a key player in Mycobacterium tuberculosis virulence but nothing has been known about its role in the diagnosis of TB. We monitored the presence of anti-PhoP antibodies in the healthy, patients and their contacts. In addition, we also measured antibodies against early secretory antigens ESAT-6 and CFP-10, and latency associated antigen Acr-1 to include proteins that are associated with the different stages of disease progression. Healthy subjects showed high antibody titer against PhoP than patients and their contacts. In addition, a distinct pattern in the ratio of Acr-1/PhoP was observed among all cohorts. This study for the first time demonstrates a novel role of anti-PhoP antibodies, as a possible marker for the diagnosis of TB and therefore will contribute in the appropriate action and management of the disease.